Effectiveness of Law and Public Policy in Facing Cyber ​​Threats to State Security - Anastasya, Vannya; S.T. Kansil, Christine (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Cybersecurity in Indonesia is still in its developmental stage and is faced with various complex challenges. One of the main challenges is unequal access to technology and the internet, which contributes to the digital divide in society. In addition, content restrictions often limit freedom of expression, while privacy and data security issues are increasingly pressing as the use of digital platforms increases. While the government has taken positive steps, such as the implementation of the Personal Data Protection Law, the effectiveness of this regulation is still in doubt due to a lack of integration in implementation. The rise in cyber incidents, including ransomware attacks targeting critical infrastructure, highlights the need for a more holistic and proactive approach. This research emphasizes the importance of strengthening the legal framework and improving cybersecurity literacy among the public. In the ever-changing digital era, striking a balance between liberalization and protection of national interests is crucial for Indonesia to optimally harness its digital potential without neglecting crucial security aspects.